1990
DOI: 10.2135/cropsci1990.0011183x003000010027x
|View full text |Cite
|
Sign up to set email alerts
|

Field Drought Tolerance of a Soybean Plant Introduction

Abstract: Rainfall is seldom sufficient to meet the evaporative and transpirational demands of a soybean crop [Glycine max (L.) Merr.] in the southeastern USA. Development of new drought‐tolerant cultivars would thus seem an effective way in which to address the problem of moisture stress. Unfortunately, few drought‐tolerant genotypes have been identified for use as breeding stock. The objective of this study was to compare the relative droughtolerance of plant introduction PI 416937, a visually slow‐wilting accession, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 0 publications
1
110
1
4
Order By: Relevance
“…Under conditions of water shortage in the soil, in which nutrient absorption, especially nitrogen absorption, is reduced, it appears that there should be a correspondence between the available water in the soil and the nitrogen applied. This will, on the one hand, reduce the cost of corn production and, on the other hand, will prevent the unnecessary application of nitrogen, which is not usually accompanied by an increase in yield (Solan et al, 1990). Therefore, in this research, we studied the effects of plant density and nitrogen application on some of the qualitative and quantitative traits of silage corn cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of water shortage in the soil, in which nutrient absorption, especially nitrogen absorption, is reduced, it appears that there should be a correspondence between the available water in the soil and the nitrogen applied. This will, on the one hand, reduce the cost of corn production and, on the other hand, will prevent the unnecessary application of nitrogen, which is not usually accompanied by an increase in yield (Solan et al, 1990). Therefore, in this research, we studied the effects of plant density and nitrogen application on some of the qualitative and quantitative traits of silage corn cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, different cultivars were showing significant difference in xylem dimension ( Figure 7) and maximum diameter was reported from the genotype number 22 while minimum from the genotype number 3 and 17 genotypes, respectively ( Figure 10C, Figure 14Q). Assimilate retranslocation is universal trait with intermediate heritability (Sloane et al, 1990).…”
Section: Radial Dimension Of Big Xylem Vessel (Rdbxv)mentioning
confidence: 99%
“…It is an indication of extra capacity to store food material, which is useful during stress conditions. According to Sloane et al (1990) yield selection in the absence of drought is an effective method to improve yield in dry areas .…”
Section: Distance Between Vascular Bundle To Epidermis (Dbvbe)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is some disagreement in the literature concerning the occurrence and importance of OA in soybean. Several studies have reported moderate levels of OA in soybean (Meyer and Boyer 1972;Cortes and Sinclair 1986;Sloane et al 1990;Morgan 1992) whereas Sionit and Kramer (1977) and Turner et al (1978) found no evidence of OA in leaves of, respectively, controlled environment or field grown plants. By analogy with pigeonpea, if OA exists in soybean, it may conceivably provide some capacity to maintain tissue water status above RWC c .…”
Section: Introductionmentioning
confidence: 99%